Effect of Headstarting Eggstrands of the Endangered Houston Toad (Bufo = [Anaxyrus] houstonensis) from a Captive Assurance Colony on Native Breeding Pond Microbiomes - Andrea Villamizar; Spandana Vemulapally; Trina Guerra; Maryanne E. Tocidlowski; Michael R. J. Forstner; Dittmar Hahn (Conservation, 2025)
The bacterial community in water from the Houston-toad captive assurance colony held at the Houston Zoo, TX, was used for comparison to the native pond bacterial composition by Ilumina-based 16S rRNA V3 amplicon sequencing. We analyzed composite sediment–water samples from native breeding ponds before and after the release of eggstrands, focusing on opportunistic pathogens of the genus Mycobacterium within the phylum Actinobacteria. Proximal native breeding ponds without headstarting were analyzed for comparison. Tank-water samples from holding facilities (NACQ, Rm1, Rm3, Rm4) showed similar bacterial profiles, with sequences identifying Proteobacteria (57.8 ± 6.2% of all reads), Bacteriodetes (28.1 ± 8.9% of all reads), and Firmicutes (4.1 ± 2.0% of all reads) generally accounting for more than 90% of all reads. Actinobacteria were identified in low abundance, accounting for 1.4 ± 1.1% of all reads, with Nocardiaceae being the most prominent group (54 to 75% of reads), followed by Microbacteriaceae (6 to 12%) and Mycobacteriaceae (1 to 3%). In the pond samples, Proteobacteria remained the most prominent phylum, comprising about 30% of all reads, though other phyla such as Acidobacteria, Actinobacteria, Bacteriodetes, Chloroflexi, Cyanobacteria, Firmicutes, Planctomycetes, Verrucomicrobia, and others were also well represented, ranging from 1% to 15%, with individual phyla peaking at specific sampling times. The prevalence of Actinobacteria sequences varied widely among ponds (<1 to 11% of all reads) and over time (10% and 1%). Most mycobacteria sequences retrieved from tank water were not detected in pond water. Thus, the potential introduction of opportunistic mycobacteria pathogens with tank water from holding facilities and eggstrands via headstarting does not seem to lead to the establishment of these bacteria in natal ponds.